Effect of molecular architecture and chemical structure on solid-state and barrier properties of heteroatom-containing aliphatic polyesters. (May 2016) - Gigli, Matteo; Lotti, Nadia; Siracusa, Valentina; Gazzano, Massimo; Munari, Andrea; Dalla Rosa, Marco
Graphical abstract: Highlights: Novel aliphatic copolyesters with ether linkages synthesized by reactive blending. Molecular architecture can be tailored by varying the mixing time. The block length influences both the thermal and mechanical behavior. Improved barrier properties to gases with respect to poly(lactic acid). Abstract: A class of multiblock fully-aliphatic copolyesters containing thio-ether linkages has been synthesized by reactive blending. Solid-state properties have been correlated to the chemical structure and the molecular architecture. With the aim of employing these polymers for food packaging, the permeability behavior to CO2 and O2 gas has been analysed. The decrease of the degree of crystallinity, due to the copolymerization, together with the flexibility given by the thio-ether containing sequences, deeply influenced the behavior of the copolymers. The length of the copolymer sequences played the major role in tailoring the polymer characteristics. A decrease in the block length caused a decrease in the crystallinity degree and in the flexibility effect. Finally, the copolyesters here presented have been compared to ether-oxygen containing samples of comparable molecular architecture, to evaluate the effect of the different heteroatom on the polymer properties.